2019
DOI: 10.1177/1090198119859420
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and the Sexual and Reproductive Health Outcomes of Women in Ghana

Abstract: Few studies have examined the relationships between intimate partner violence (IPV) and the sexual and reproductive health outcomes of women in sub-Saharan countries in general and Ghana specifically. This study began to fill the gap by investigating whether individual- and community-level IPV influenced unwanted pregnancy and pregnancy loss among women in Ghana. Nationally representative cross-sectional data were collected from 2,289 ever-married women, and multilevel modeling was used to estimate individual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
4
14
0
Order By: Relevance
“…It is also documented that women who experience IPV are less motivated to access or utilize contraceptives [ 24 ]. Using demographic and health survey data, Tenkorang [ 25 ], Silverman et al [ 26 ], and Tsai et al [ 27 ] have examined the associations between IPV and sexual and reproductive health outcomes, including family planning use in Ghana, Niger, and the Philippines, respectively. While Tenkorang [ 25 ] found significant associations between IPV and sexual and reproductive health outcomes (unwanted pregnancy and a pregnancy loss) and Silverman et al [ 26 ] found significant associations between IPV and non-use of family planning, the study by Tsai et al [ 27 ], concluded that there was no association between IPV and non-use of family planning.…”
Section: Introductionmentioning
confidence: 99%
“…It is also documented that women who experience IPV are less motivated to access or utilize contraceptives [ 24 ]. Using demographic and health survey data, Tenkorang [ 25 ], Silverman et al [ 26 ], and Tsai et al [ 27 ] have examined the associations between IPV and sexual and reproductive health outcomes, including family planning use in Ghana, Niger, and the Philippines, respectively. While Tenkorang [ 25 ] found significant associations between IPV and sexual and reproductive health outcomes (unwanted pregnancy and a pregnancy loss) and Silverman et al [ 26 ] found significant associations between IPV and non-use of family planning, the study by Tsai et al [ 27 ], concluded that there was no association between IPV and non-use of family planning.…”
Section: Introductionmentioning
confidence: 99%
“…This power imbalance in the family leaves the female partner vulnerable to abuse. In the Ghanaian context, men are seen as the heads of the family and so whatever they say should not be challenged (Apatinga & Tenkorang, 2020;Dako-Gyeke et al, 2019;Dery, 2019;Owusu-Addo et al, 2018;E. Y. Tenkorang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other authors have found similar results (Machisa et al, 2018;Sabri et al, 2019;Eric Y. Tenkorang, Owusu, Yeboah, & Bannerman, 2013) as factors that led to intimate partner violence. In most cultures, men control and dominate their partners in Ghana (Dickson et al, 2020;Issahaku, 2015;Owusu-Addo et al, 2018;E. Y. Tenkorang, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations